Water Quality Index for the River Kagina at Shahabad (India) - Ganesh, Dr. Sumer Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
River Kagina water quality, a tributary of the Mullamari, Bennithora & Kamalavathi flows are the a main tributaries to this river .system was calculated using water quality index (WQI).based on several parameters, the key index provides and states quality of water at point location. A goal of water quality indexes is to translate complex water quality data into information that is logical and useful for public. Different parameters are used to calculate the pH, (TDS), Th, Ca, Mg, alkalinity, (DO), (No3) & (Cl). The Kagina’s WQI values ranged from 34.35to 38.26. WQI values less than 50 indicates water are free from impurities.